THE IMPACTS OF SERVICE QUALITY ON THE CUSTUMERS LOYALITY OF CONVENTIONAL BANK IN BANDA ACEH - Nurbismi Nurbismi (SI-MEN, 2015)
The aims of this research are (1) to know the impacts of services quality providedby conventional bank officers an their custumers loyality in Banda Aceh,(2) to find out thedominant factors that can influence the custumers loyality of conventional bankes in BandaAceh.This research was done in Banda Aceh and involed the custumers of someconventional banks, such as, (1) BRI, (2) BNI,(3) Mandiri Bank, (4).BII, (5) BCA, (6)Danamon Bank, (7) Bukopin Bank, (8) Permata Bank witer 100 respondent.Based on the research result, its found that, the value Fhitung > Ftabel [50.725 >2.311] on the level of significance  = 5%, it shown simultaneously that the variatte wasinfluential at the custumers loyalty of convensional bank in Banda Aceh, whereas,partially, the variabels that gave dominant impact were variabels of responses andrealization provided by conventional bank officers in Banda Aceh, since its fond that itsregresion coefficient of other variables.